Plasma D-dimer levels are a biomarker for in-hospital complications and long-term mortality in patients with traumatic brain injury - Chen, Xinli; Wang, Xiaohua; Liu, Yingchao; Guo, Xiumei; Wu, Fan; Yang, Yushen; Hu, Weipeng; Zheng, Feng; He, Hefan (Frontiers in Molecular Neuroscience, 2023)
Introduction Traumatic brain injury (TBI) is a major health concern worldwide. D-dimer levels, commonly used in the diagnosis and treatment of neurological diseases, may be associated with adverse events in patients with TBI. However, the relationship between D-dimer levels, TBI-related in-hospital complications, and long-term mortality in patients with TBI has not been investigated. Here, examined whether elevated D-dimer levels facilitate the prediction of in-hospital complications and mortality in patients with TBI. Methods Overall, 1,338 patients with TBI admitted to our institute between January 2016 and June 2022 were retrospectively examined. D-dimer levels were assessed within 24 h of admission, and propensity score matching was used to adjust for baseline characteristics. Results Among the in-hospital complications, high D-dimer levels were associated with electrolyte metabolism disorders, pulmonary infections, and intensive care unit admission (p < 0.05). Compared with patients with low (0.00–1.54 mg/L) D-dimer levels, the odds of long-term mortality were significantly higher in all other patients, including those with D-dimer levels between 1.55 mg/L and 6.35 mg/L (adjusted hazard ratio [aHR] 1.655, 95% CI 0.9632.843), 6.36 mg/L and 19.99 mg/L (aHR 2.38, 95% CI 1.416–4.000), and >20 mg/L (aHR 3.635, 95% CI 2.195–6.018; p < 0.001). D-dimer levels were positively correlated with the risk of death when the D-dimer level reached 6.82 mg/L. Conclusion Overall, elevated D-dimer levels at admission were associated with adverse outcomes and may predict poor prognosis in patients with TBI. Our findings will aid in the acute diagnosis, classification, and management of TBI.